2021
DOI: 10.5539/ijbm.v16n9p107
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Finance as Social Finance: A Bibliometric Analysis from 2000 to 2021

Abstract: The main purpose of this research is to map the academic contribution of social finance to the discussion in the field of Islamic finance. An analysis of 788 contributions published in international academic journals, books review and chapters, editorial material and proceedings papers has been done using the bibliometric method. The findings show that there are a number of journals that have had a higher production on the topic with an impact on research and, furthermore, it emerges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…First, this research complement the result of previous studies such as bibliometric analysis of social finance (E. A. Firmansyah & Faisal, 2020;Hariyanto & Hamzah, 2022;Rusydiana, Taqi, et al, 2021;Srisusilawati et al, 2021), Social finance is carried out by (Ismail & Aisyah, 2021;Lanzara, 2021;Purnama Sari et al, 2022;Secinaro et al, 2021) by taking the point of view of accounting treatment. Second, combining zakat, infaq/alms accounting with waqf accounting to become Islamic social financial accounting, as far as authors' knowledge there is no or has not yet been found a research that directly raises the theme of Islamic social financial accounting.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…First, this research complement the result of previous studies such as bibliometric analysis of social finance (E. A. Firmansyah & Faisal, 2020;Hariyanto & Hamzah, 2022;Rusydiana, Taqi, et al, 2021;Srisusilawati et al, 2021), Social finance is carried out by (Ismail & Aisyah, 2021;Lanzara, 2021;Purnama Sari et al, 2022;Secinaro et al, 2021) by taking the point of view of accounting treatment. Second, combining zakat, infaq/alms accounting with waqf accounting to become Islamic social financial accounting, as far as authors' knowledge there is no or has not yet been found a research that directly raises the theme of Islamic social financial accounting.…”
Section: Introductionsupporting
confidence: 68%
“…Firmansyah & Faisal, 2020;Hariyanto & Hamzah, 2022;Rusydiana, Taqi, et al, 2021;Srisusilawati et al, 2021). Social finance is carried out by (Ismail & Aisyah, 2021;Lanzara, 2021;Purnama Sari et al, 2022;Secinaro et al, 2021). At the same time, some of bibliometric analysis of Islamic accounting has been done by researchers such as Islamic accounting in general (Hassan et al, 2021;Rusydiana, Taqi, et al, 2021;Ryzky & Rini, 2018), and on shariah auditing (Handoko & Mardian, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that boundaries need to be explored in the future. For instance, some of the related research in bibliometric are focusing on Islamic banking and finance (Biancone et al , 2020; Hassanein and Mostafa, 2022), Islamic finance (Bollani and Chmet, 2020; Çürük and Kaynar, 2021; Tijjani et al , 2020), Islamic economics and finance (Handoko, 2020; Rusydiana et al , 2021), Islamic social finance (Lanzara, 2021; Sari et al , 2022), fintech (Alshater et al , 2022; Aysan and Unal, 2021) and efficiency in Islamic banking (Shah et al , 2021). Bibliometric research focusing on ICM is scarce.…”
Section: Methodsmentioning
confidence: 99%
“…To achieve the aim of this paper, we modified several previous review papers and adopted the suggestion to use a structured literature review by focusing on specific search and select strategies [ 35 ], knowledge of previous review papers on Islamic finance and IB [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 6 ], Islamic social finance [ 44 , 45 , 46 , 47 , 14 ] and the literature on Islamic endowment funds (Awqaf or waqf) as part of Islamic social finance [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. However, in exploring the current and emerging trends in the IISCF literature, we present a novel methodology of combining a systematic literature review (SLR) and bibliometric analysis to strengthen the result of the literature review published from 1979 to 2023.…”
Section: Introductionmentioning
confidence: 99%